2011
DOI: 10.1111/j.1439-0531.2010.01647.x
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Dynamics and Oestrous Detection in Thai Postpartum Swamp Buffaloes (Bubalus bubalis)

Abstract: This study characterized follicular activity and oestrous behaviour from 5 to 9 days post-calving up to the 4th ovulation postpartum (pp) in 16 multiparous (range 2-7 parities) Thai swamp buffalo cows (Bubalus bubalis), aged 4-12 years and weighing from 432 to 676 kg. Ovarian follicular activity was examined by transrectal ultrasonography (TUS) every morning. Oestrous detection was performed twice daily by direct personal observation of behaviour and for presence of clear cervical mucus discharge and indirectl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 15 publications
4
21
0
5
Order By: Relevance
“…Similar findings were also reported, in Iraqi buffaloes by Azawi et al (2009), who reported the POF size, on the right and left ovaries as 10.78 and 11.24±2.15 mm, respectively. Barkawi et al (2009) reported the maximum diameter of POF as 14-15 mm in Egyptian buffaloes whereas Yindee et al (2011) in swamp buffaloes revealed the presence of ovulatory follicles with a mean diameter of 13.5±0.52 to 14.17±1.08 mm during the post-partum ovulations. Contrary to the present findings, Derar et al (2012) reported the POF size as 9.8±0.32 mm in Egyptian buffaloes which was much lower than the present observations.…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings were also reported, in Iraqi buffaloes by Azawi et al (2009), who reported the POF size, on the right and left ovaries as 10.78 and 11.24±2.15 mm, respectively. Barkawi et al (2009) reported the maximum diameter of POF as 14-15 mm in Egyptian buffaloes whereas Yindee et al (2011) in swamp buffaloes revealed the presence of ovulatory follicles with a mean diameter of 13.5±0.52 to 14.17±1.08 mm during the post-partum ovulations. Contrary to the present findings, Derar et al (2012) reported the POF size as 9.8±0.32 mm in Egyptian buffaloes which was much lower than the present observations.…”
Section: Resultsmentioning
confidence: 99%
“…The time for resumption of ovarian activity is important for reduction of post‐partum anoestrus and calving interval in buffaloes (El‐Wishy, ; Kandiel, Gad, Sosa, & El‐Azab, ; Yindee et al., ). Hormonal and metabolic changes during the peri‐parturient period and especially after calving have an important impact on post‐partum follicular development and ovulation (Hussein, Senosy, & Abdellah, ; Prakash et al., ; Terzano, Barile, & Borghese, ).…”
Section: Introductionmentioning
confidence: 99%
“…Hormonal and metabolic changes during the peri‐parturient period and especially after calving have an important impact on post‐partum follicular development and ovulation (Hussein, Senosy, & Abdellah, ; Prakash et al., ; Terzano, Barile, & Borghese, ). Earlier development of a large follicle has been associated with better resumption of ovarian activity and resulted in effective reproductive performance (Malik et al., ; Yindee et al., ; Yotov & Atanasov, ). The reported intervals between calving and initiation of follicular activity in buffaloes varied from 7 days (Presicce, Bella, Terzano, De Santis, & Senatore, ), 10 days (Lohan, Malik, & Kaker, ), 14 days (Hussein et al., ) to 30 days (Usmani, Dailey, & Inskeep, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors reported that the administration of hormones include PMSG, GnRH, Progesterone or hCG during early postpartum period has conception (8), (9). The effect of ovarian inactivity is including increase period of first estrus postpartum, number of services per conception, pregnancy rate and days open (7),(10),(11), (12) ,(13). The purposes of this study were to evaluate different hormonal regimes for treatment ovarian inactivity and the effects on reproductive parameters (response animal, services per conception , pregnancy rate, days open) to improvement the reproductive performance in Iraqi buffaloes.…”
Section: Introductionmentioning
confidence: 99%